Characteristics of K + Outward Currents in the Cochlear Outer Hair Cells of Circling Mice within the First Postnatal Week - Ahn, Ji Woong; Kang, Shin Wook; Ahn, Seung Cheol (The Korean journal of physiology & pharmacology, 2015)
K(+) outward currents in the outer hair cells (OHCs) of circling mice (homozygous (cir/cir) mice), an animal model for human deafness (DFNB6 type), were investigated using a whole cell patch clamp technique. Littermate heterozygous (+/cir) mice of the same age (postnatal day (P) 0 -P6) were used as controls. Similar slow rising K(+) currents were observed in both genotypes, but their biophysical and pharmacological properties were quite different. The values of Vhalf for activation were significantly different in the heterozygous (+/cir) and homozygous (cir/cir) mice (-8.1±2.2 mV, heterozygous (+/cir) mice (n=7) and -17.2±4.2 mV, homozygous (cir/cir) mice (n=5)). The inactivation curve was expressed by a single first order Boltzmann equation in the homozygous (cir/cir) mice, while it was expressed by a sum of two first order Boltzmann equations in the heterozygous (+/cir) mice. The K(+) current of homozygous (cir/cir) mice was more sensitive to TEA in the 1 to 10 mM range, while the 4-AP sensitivities were not different between the two genotypes. Removal of external Ca(2+) did not affect the K(+) currents in either genotype, indicating that the higher sensitivity of K(+) current to TEA in the homozygous (cir/cir) mice was not due to an early expression of Ca(2+) activated K(+) channels. Our results suggest that the K(+) outward current of developing homozygous (cir/cir) mice OHCs is different in both biophysical and pharmacological aspects than that of heterozygous (+/cir) mice.